Análisis del impacto económico y social de la afiliación al Sistema Integral de Seguridad Social de las empleadas domésticas en Ecuador: una comparación entre los años 2010 y 2016 - Macas Vivanco, Sharon Estefania (2020)
This thesis entitled “Analysis of the economic and social impact of the affiliation to the Integral Social Security System of domestic workers in Ecuador: a comparison between 2010 and 2016”, had as a general objective: To evaluate the economic and social impact of the affiliation to the Comprehensive Social Security System in domestic workers in Ecuador, through a gap decomposition model and a propensity score matching in 2010 and 2016. Thus, a methodology based on the methods was proposed: inductive, analytical and statistical. Among the techniques used are: bibliographic and statistical. Also among the instruments used for data collection are: the bibliographic record and the software package that was used for data analysis and the generation of variables. These data were obtained from the ENEMDU (2011 and 2016), which once the formulas were replaced, allowed us to know the diversification of salaries received by domestic workers, depending on the age, ethnicity and geographical area where they provide their services. Likewise, it was evident that before the Social Security Law for domestic workers was put into practice, their salaries were low and that when their salary was applied they increased considerably, causing a positive effect.